Legal regulation of the launch and the organization of games of the circus in ancient Rome to the Principate - Magdolna Gedeon (Journal on European History of Law, 2011)
In the ancient Roman sources we can find many legal rules relating to the organization of the circus games. In the regal period the king himself initiated and organised the new games in veneration of the gods. The ludi votivi and the ludi publici were established during the Republic. The organization of these games were the duty of the consuls and the aediles.